The Rho-related protein Rnd1 inhibits Ca(2+) sensitization of rat smooth muscle - Loirand, Gervaise (Blackwell Science Inc, 1999)
1. The small GTP-binding Rho proteins are involved in the agonist-induced Ca(2+) sensitization of smooth muscle. The action and the expression of Rnd1, a new member of the Rho protein family constitutively bound to GTP, has been studied in rat smooth muscle. 2. Recombinant prenylated Rnd1 (0.01-0.1 mg ml(−1)) dose dependently inhibited carbachol- and GTPγS-induced Ca(2+) sensitization in β-escin-permeabilized ileal smooth muscle strips but had no effect on the tension at submaximal [Ca(2+)] (pCa 6.3). Rnd1 inhibited GTPγS-induced tension without shifting the dose-response curves to GTPγS. 3. pCa-tension relationships were not modified by Rnd1 and the rise in tension induced through the inhibition of myosin light chain phosphatase by calyculin A was not affected by Rnd1. 4. The Ca(2+) sensitization induced by recombinant RhoA was completely abolished when RhoA and Rnd1 were applied together. 5. Rnd1 was expressed at a low level in membrane fractions prepared from intestinal or arterial smooth muscles. The expression of Rnd1 was strongly increased in ileal and aortic smooth muscle from rats treated with progesterone or oestrogen. Progesterone-treated ileal muscle strips showed a decrease in agonist-induced Ca(2+) sensitization. 6. The present study shows that (i) Rnd1 inhibits agonist- and GTPγS-induced Ca(2+) sensitization of smooth muscle by specifically interfering with a RhoA-dependent mechanism and (ii) an increase in Rnd1 expression may account, at least in part, for the steroid-induced decrease in agonist-induced Ca(2+) sensitization.